Daylight from solar radiation / Abdul Halim Othman and Basri Ibrahim - Othman, Abdul Halim; Ibrahim, Basri (1997)
The relationship between solar radiation and illumination fully in a horizontal surface at Shah Alam is studies. Since this is the first time illumination is measured in this country, a photometer (luxmeter ) is installed on the roof top of a building at the School of Applied Science, Institut Teknologi MARA, Shah Alam. The photometer and a standard pyranometer are connected to a data logger and the measured data are downloaded with a computer. The data are plotted onto chart and a regression analysis was done to determine the relationship between solar radiation and illumination. The relationship is found be a linear and produce an equation y = 0.99x + 32.4.